Development of a molecular marker for bacterial wilt resistance in brinjal ( solanum melongene L.) varieties surya and swetha. - Somya P P (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2011)
The study entitled ‘Development of a molecular marker for bacterial wilt resistance in brinjal (Solanum melongena L.) varieties Surya and Swetha’ was carried out at the Centre for Plant Biotechnology and Molecular Biology (CPBMB), College of Horticulture, Vellanikkara during the period 2009-2011.